Pentingnya Integritas Akademik - Ruzika Hafizha (Ma'soem University, 2021)
Academic integrity is the most important thing in realizing educational goals Every student, educator, and school staff are required to uphold the values of academic integrity. Academic integrity is a commitment to academic values that are manifested in behaviors, namely honesty, trust, justice, respect, and responsibility in carrying out academic demands. Academic integrity is an academic culture that needs to be maintained. Low academic integrity leads to various academic violations such as plagiarism, data falsification, dishonesty and cheating during exams or tests. Each educational institution certainly has its own code of honor in solving problems of academic violations and maintaining the honor of their educational institution. The research method used is a literature study research method. This article aims to obtain an overview of the definition of academic integrity, characteristics of academic integrity, and the factors that affect academic integrity.